2016
DOI: 10.3390/lubricants4030028
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Anti-Wear Tribofilms via α-ZrP Nanoplatelet as Lubricant Additives

Abstract: Abstract:Effective tribofilms are desirable to protect mechanical systems. In the present research, we investigated the formation of a tribofilm through the use of α-ZrP (Zr(HPO 4 ) 2¨H2 O) as an additive. Experiments were conducted on a base oil where 0.2 wt% of the additive was used. Experimental results showed a 50% reduction in friction and a 30% reduction in wear when compared to the base oil containing 0.8 wt% ZDDP. Spectroscopic characterization indicated that the tribofilm consists of iron oxide, zirco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…It is known that phosphate groups may act as lubricants (Yang et al, 2016), reducing the frictional force resisting to the relative sliding movement between neighboring surfaces, which is transduced in a lower COF. Furthermore, under wear action, PO 4 3ions are known to undergo favorable reactions resulting in protective tribofilms (Somers et al, 2013;Dai et al, 2016). This might explain the smoothening effect observed on the surface of the tribofilm.…”
Section: Tribocorrosion Degradation Of Tio 2 Nanotubular Films Under mentioning
confidence: 99%
“…It is known that phosphate groups may act as lubricants (Yang et al, 2016), reducing the frictional force resisting to the relative sliding movement between neighboring surfaces, which is transduced in a lower COF. Furthermore, under wear action, PO 4 3ions are known to undergo favorable reactions resulting in protective tribofilms (Somers et al, 2013;Dai et al, 2016). This might explain the smoothening effect observed on the surface of the tribofilm.…”
Section: Tribocorrosion Degradation Of Tio 2 Nanotubular Films Under mentioning
confidence: 99%
“…It also decreased the COF of ZDDP‐derived tribofilm when compared with base oil and boric acid+base oil. Calcium is added into ZDDP as a detergent; however, in a higher level of concentrations such as ≥ % 2, it reacts with ZDDP and forms Ca‐PO and CCO 3 compounds, which Pawlak and Dai reported that these tribocompounds act as an antiwear agent …”
Section: Discussionmentioning
confidence: 99%
“…walled carbon nanotubes mixed nanofluids. The GnP has a two-dimensional structure with multiple plates and has weak Vander wall forces between these nanolayers (Dai et al, 2016). The sheet-like structures act as a third body solid lubricant, which has high strength and shear capabilities making the rubbing surfaces smoother.…”
Section: Analysis Of Wear Depth Using Mwcnt and Gnp Mixed Nanofluidsmentioning
confidence: 99%